How Listening YouTube Song Habit Influences Students’ Vocabulary Mastery: A Correlational Study - Abudi, Oxa Oktaviana; Hasan, Jhems Richard; Helingo, Adimawati (Institut Agama Islam Negeri (IAIN) Manado, 2024)
Vocabulary mastery is essential for students to be able to communicate well in English. However, some students still struggle memorizing new words and identifying vocabulary meanings. This study aims to determine the correlation between students' habits of listening to English YouTube songs and their vocabulary mastery. The research used a quantitative correlational approach involving 24 tenth-grade students at SMA N 1 SUWAWA. The data collection was done using a questionnaire about listening habits to English songs and a vocabulary test. The data analysis was performed using the Pearson Product Moment formula. The result showed that there is a moderate positive correlation between the habit of listening to English YouTube songs and the mastery of vocabulary of SMA N 1 Suwawa tenth-grade students (r = 0.529). This indicates that the more intense the students' habit of listening to English YouTube songs, the better their vocabulary mastery. Listening habit contributes 27.98% to the mastery of vocabulary. Based on these results, it can be concluded that there is a moderate correlation between listening habit to English YouTube songs and vocabulary mastery of tenth grade students at SMA N 1 Suwawa. The more students listen to English songs, the better they master vocabulary.Keywords: listening Habit, YouTube song, vocabulary mastery